Media Informasi sebagai Pengenalan Batik Magelang - Dyah Pikaeksi; Patra Aditia (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
Batik is an Indonesian cultural heritage that has a variety of unique and different motifs in each region. Batik Magelang is still a relatively new batik culture compared to other areas so that if put in the category of groups of motifs lifted inland because of cultural elements and the natural conditions in the city. Because there is no history or ancestors batik make batik Magelang less enjoyable and less popular than the classic motif. The lack of information and marketing into the causes of the lack of knowledge about batik Magelang.The method used for data collection is library research, observation for some communities batik and batik artisans in Magelang, and interviews of business owners and makers of batik motifs in Magelang City.This design concept is to create a medium of information to provide knowledge and information about batik motifs Magelang. In this design, the author makes the information book because the book easy to carry around, and can accommodate a lot of information. It is expected that from this design can introduce a variety of batik motif Magelang Magelang that can be appreciated and preserved by the community.